2023
DOI: 10.1186/s40545-023-00583-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmacist interventions, follow-up frequency and default on glycemic control in Diabetes Medication Therapy Adherence Clinic program: a multicenter study in Malaysia

Abstract: Background Pharmacist’s involvement in optimizing medication adherence among diabetic patients has been implemented for over a decade. Diabetes Medication Therapy Adherence Clinic (DMTAC) was set up to educate diabetic patients, monitor treatment outcomes, and manage drug-related problems. While evidence shows that pharmacist-led DMTAC was effective in reducing HbA1c, there was limited data regarding the impact of different intervention types and default to follow-up on glycemic control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(25 reference statements)
3
3
0
Order By: Relevance
“…An average decrease in diastolic blood pressure (DBP) in patients in the control arm was identified as being 3.69 mmHg ( p < 0.001), whereas such a reduction was 7.58 mmHg (p < 0.001, η 2 0.09) in patients in the intervention arm. These observations from the present study are consistent with the findings of research conducted by Lim et al ( 9 ), according to Lim et al ( 9 ) the decrease in average mean SBP was 3.55 mmHg. In the control arm, it was increased up to 5.76 mmHg, which was considered uncontrolled blood pressure, according to CPG Malaysia.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…An average decrease in diastolic blood pressure (DBP) in patients in the control arm was identified as being 3.69 mmHg ( p < 0.001), whereas such a reduction was 7.58 mmHg (p < 0.001, η 2 0.09) in patients in the intervention arm. These observations from the present study are consistent with the findings of research conducted by Lim et al ( 9 ), according to Lim et al ( 9 ) the decrease in average mean SBP was 3.55 mmHg. In the control arm, it was increased up to 5.76 mmHg, which was considered uncontrolled blood pressure, according to CPG Malaysia.…”
Section: Discussionsupporting
confidence: 94%
“…However, the reduction in HbA1c specifically among patients in the intervention group, was considerably greater compared to patients in the control group due to the collaborative care involving pharmacists. These results are in line with a randomized controlled study in clinical research by Lim et al ( 9 ), according to which the decrease in average HbA1c in the intervention group was 0.91 and 0.08% in the control group, which is statistically significant ( p ≤ 0.011) among both groups. The observations of the present study are consistent with the randomized controlled trial conducted by Butt et al ( 11 ), which was conducted in the “Universiti Kebangsaan Malaysia Medical Centre (UKMMC) in Malaysia.” HbA1c in the study subjects was reduced significantly, from 9.677 to 8.48% ( p ≤ 0.001) in the intervention arm of the study; however, no statistical reduction in HbA1c was observed in the control arm of the study (9.64–9.26%, p = 0.14).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Extensive global studies have demonstrated the effectiveness of pharmacist-based interventions on patients with diabetes, resulting in improved quality of care and clinical outcomes 23 26 28–30. In addition, several systematic reviews31–34 have identified various non-pharmacological pharmacist-led interventions, such as diabetes education,35–38 medication review,39 drug counselling/advice,40 41 lifestyle modification, self-care, peer support and behavioural intervention 42–44…”
Section: Introductionmentioning
confidence: 99%